Durability of Lightweight Aggregate Concrete Panel for Modular Housing Construction - Jurnal Dosen, Fahrizal Zulkarnain; Jurnal Dosen, Mahyuddin Ramli (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
Durability can be defined as the ability of material to withstand the effects of its environment. In the building material its may be interpreted as chemical attack, water absorption and carbonation. Chemical attack usually encountered as aggressive ground-water, particularly sulphate, polluted air and spillage of reactive liquids. A chemical aspect of durability is the stability of the material itself, particularly in the presence of moisture. Because the pore system in lightweight aggregate is generally discontinuous, the porosity of the aggregate particles themselves does not influence the permeability of concrete, which is controlled by the permeability of the hardened cement paste. Although lightweight aggregate particles are hard and therefore resistant to abrasion the open pores on the surface of the aggregate mean that, once the aggregate has become exposed, the contact surface is reduced compared with non-porous aggregate. On balance, the abrasion resistance of lightweight aggregate concrete may, therefore, be reduced in comparison with that of normal weight concrete of similar strength.